Global Estimates in Orlicz Spaces for p-Laplacian Systems in RN (Journal of Partial Differential Equations, 2020)
In this paper we obtain global estimates in Orlicz spaces for weak solutions of p-Laplacian systems in R^N for N≥ 2. Our results improve the known results for such problems.
Keywords: Orlicz space; global; gradient; p-Laplacian; systems